1986
DOI: 10.1161/01.res.58.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Replication of smooth muscle cells in vascular disease.

Abstract: SUMMARY. Smooth muscle proliferation has been recognized as central to the pathology of both major forms of vascular disease: atherosclerosis and hypertension. Recent advances in our knowledge of mechanisms of control of proliferation suggest that events occurring in adult animals may recapitulate portions of the developmental biology of the smooth muscle cell. This review attempts to consider the current state of knowledge of the mechanisms controlling smooth muscle proliferation in these two diseases, to put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
378
1
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 680 publications
(392 citation statements)
references
References 159 publications
9
378
1
4
Order By: Relevance
“…This is underscored by the observation that a microsatellite polymorphism in the promoter region of the HO-1 gene that is linked to decreased inducibility is associated with restenosis and increased vascular inflammation after percutaneous transluminal angioplasty, susceptibility to coronary artery disease in type 2 diabetic patients and in Japanese patients with coronary risk factors, and the development of abdominal aortic aneurysms (Exner et al, 2001;Chen et al, 2002;Kaneda et al, 2002;Schillinger et al, 2002a,b). Since excessive growth of vascular SMCs is an important contributing factor to a number of vascular disease states, including restenosis following angioplasty, atherosclerosis, and hypertension (Zierler et al, 1982;Ross, 1986;Schwartz et al, 1986), increasing HO-1 expression in blood vessels may offer a promising approach in treating vascular disorders. As shown in Figure 2, the expression of HO-1 in SMCs may block the growth of vascular SMCs via multiple mechanisms.…”
Section: Ho-1 As a Therapeutic Target In Vascular Diseasementioning
confidence: 99%
“…This is underscored by the observation that a microsatellite polymorphism in the promoter region of the HO-1 gene that is linked to decreased inducibility is associated with restenosis and increased vascular inflammation after percutaneous transluminal angioplasty, susceptibility to coronary artery disease in type 2 diabetic patients and in Japanese patients with coronary risk factors, and the development of abdominal aortic aneurysms (Exner et al, 2001;Chen et al, 2002;Kaneda et al, 2002;Schillinger et al, 2002a,b). Since excessive growth of vascular SMCs is an important contributing factor to a number of vascular disease states, including restenosis following angioplasty, atherosclerosis, and hypertension (Zierler et al, 1982;Ross, 1986;Schwartz et al, 1986), increasing HO-1 expression in blood vessels may offer a promising approach in treating vascular disorders. As shown in Figure 2, the expression of HO-1 in SMCs may block the growth of vascular SMCs via multiple mechanisms.…”
Section: Ho-1 As a Therapeutic Target In Vascular Diseasementioning
confidence: 99%
“…The proliferation of smooth muscle cells in vitro is stimulated by various mitogens such as PDGF, IGF-1, basic fibroblast growth factor, EGF, IL-1, and TGF-f3 (1)(2)(3). The binding of growth factors to specific receptors on smooth muscle cells initiates a complicated series of biochemical reactions which involve protein kinase C, receptor-linked tyrosine phosphorylation, and cAMP-dependent kinases (4).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the growth response in a number of cell types, including smooth muscle cells, to serum mitogens in vitro is suppressed by antisense oligonucleotides directed against c-myc, c-myb, proliferating cell nuclear antigen (PCNA),' cyclins, and non- 1. Abbreviations used in this paper: PCNA, proliferating cell nuclear antigen; SV40LT-SMC, smooth muscle cell line immortalized with SV40 large T antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Dedifferentiation of vascular smooth muscle cells (VSMCs), followed by their migration from media to intima and proliferation in intima, contribute to the pathophysiology of renarrowing of the artery after angioplasty (15,16). Previously, we have shown that NFATs play a role in the regulation of VSMC growth and migration (17,18).…”
mentioning
confidence: 99%